2012
DOI: 10.1002/jwmg.456
|View full text |Cite
|
Sign up to set email alerts
|

Summer tree roost selection by Rafinesque's big‐eared bat

Abstract: Roost requirements of most North American forest bats are well-documented, but questions remain regarding the ultimate mechanisms underlying roost selection. Hypotheses regarding roost selection include provision of a stable microclimate, space for large colonies, protection from predators, and proximity to foraging habitat, among others. Although several hypotheses have been proposed, specific mechanisms likely vary by species and geographic region. Rafinesque's big-eared bat (Corynorhinus rafinesquii) common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…In most instances, 2 people inspected each cavity. Previous studies indicated that the probability of detecting Rafinesque's big-eared bats when they are present was 91-96% via inspection by 2 observers (Clement and Castleberry 2013;Fleming et al 2013b). The species, number, and position within the cavity (low, middle, or top) of all bats were recorded as were the species, DBH, tree height, decomposition state (live or dead), inside cavity dimensions (if possible), cavity texture, and cavity opening location (basal, basal and chimney, chimney only) of each potential roost tree.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most instances, 2 people inspected each cavity. Previous studies indicated that the probability of detecting Rafinesque's big-eared bats when they are present was 91-96% via inspection by 2 observers (Clement and Castleberry 2013;Fleming et al 2013b). The species, number, and position within the cavity (low, middle, or top) of all bats were recorded as were the species, DBH, tree height, decomposition state (live or dead), inside cavity dimensions (if possible), cavity texture, and cavity opening location (basal, basal and chimney, chimney only) of each potential roost tree.…”
Section: Methodsmentioning
confidence: 99%
“…Although we could not examine trees with chimney or upper bole cavities, these trees were included in the survey and in some of the analyses as they represent alternate roosts. All trees with basal cavity openings were inspected but only those with cavities > 2 m high and > 30 cm wide were included in the survey as smaller cavities are unlikely to be used (Clement and Castleberry 2013). Each tree with a sufficiently large cavity was marked with a numbered aluminum tag and its location was recorded with the Trimble GEO-XT GPS unit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations